Setting the Stage: Pre-Trip Preparation for Short-Term Immersion Programs. Issue 1 (1st January 2019) - Rowan-Kenyon, Heather T.; Knight, Sarah; McCready, Adam
Abstract : The authors examine components of pre-trip preparation that influence student trip experiences and learning related to short-term immersion programs. With the use of a transformative learning framework and a multisite longitudinal case study, key components emerged as essential in preparing students for these experiences: community building, learning about social justice issues and trip location, trip leader training, and fundraising.